Development and psychometric validation of an instrument to identify barriers to self-care among Spanish patients with Type 2 Diabetes on the basis of Theory of Planned Behavior - Caro-Bautista, Jorge; Espinar-Toledo, Milagrosa; Villa Estrada, Francisca; Kaknani-Uttumchandani, Shakira; García-Mayor, Silvia; salas-samper, felipe; Morales-Asencio, José Miguel (ELSEVIER, 2019)
Objectives: To develop and psychometrically validate a questionnaire to identify barriers to self-care in this population on the basis of the theory of planned behavior. Methods: The study was carried out in 15 primary healthcare centers belonging to the Public Health Care System in Andalusia (Spain). After content validity was confirmed, an initial pilot study was undertaken (n = 54) and the model was evaluated in 2 samples of 205 subjects each to test its configural and metric invariance by confirmatory factor analysis. Internal consistency, test-retest reliability, criterion validity, and interpretability were carried out following COSMIN standards. Results: A 4-factor instrument (intention, subjective norms, perceived control, and attitudes) with 15 items was obtained with a good fit: goodness-of-fit index = 0.92, comparative fit index = 0.93, and root mean square error of approximation = 0.043 (90% confidence interval 0.034-0.052). Cronbach a was 0.78, and test-retest reliability was adequate (intraclass correlation coefficient 0.73; P , .0001). The instrument revealed an adequate criterion validity depending on the treatment complexity and level of metabolic control. Thus, participants with poor self-care scores were more likely to suffer from diabetes-related complications (odds ratio 1.91; 95% confidence interval 1.15-3.1). Conclusions: A theory-driven instrument is suitable for its use with Spanish people with type 2 diabetes to assess their selfcare needs and make tailored recommendations for lifestyle modifications on the basis of their behavioral determinants.
Keywords: Diabetes tipo 2; instrument development; psychometric validation; self-care; theory of planned behavior; type 2 diabetes mellitus